Pengaruh Model Problem Based Learning Terhadap Kemampuan Numerasi Murid Fase E Pada Materi Daur Biogeokimia - Nurazizarah Matul Putri; Syamsurizal Syamsurizal (Al-Alam: Islamic Science Education Journal, 2026)
This study aims to analyze the effect of the Problem-Based Learning (PBL) model on the numeracy skills of Phase E students regarding the topic of biogeochemical cycles. The study employed a quantitative approach using a quasi-experimental method and a posttest-only control group design. The sample consisted of an experimental class implementing the PBL model and a control class using Direct Instruction. The research instrument was a validated 30-item multiple-choice numeracy test. Data were analyzed using normality tests, homogeneity tests, and an independent samples t-test with the aid of SPSS. The results showed that the mean posttest score of the experimental class (83.89) was higher than that of the control class (75.93). Hypothesis testing yielded a significance value of 0.000 (<0.05), indicating a significant difference between the two classes. The implementation of the PBL model proved effective in enhancing students' numeracy skills through active engagement in problem-solving, discussion, and data analysis. Thus, the PBL model serves as an effective alternative instructional approach for improving students' numeracy skills in the study of biogeochemical cycles.